Optimization of UV-Induced Graft Polymerization of Acrylic Acid on Polypropylene Films Using CdS as Light Sensor - Stragliotto, María Fernanda (2018)
Photoconductive cell of CdS was used to optimize the photograft polymerization of acrylic acid (AA) onto polypropylene film surface. Effect of UV-light intensity on the performance of this reaction in the three-dimensional space inside the reactor was researched. A relationship between light intensity measured as conductance and performance of the AA graft reaction was found. In addition, a linear relationship (r2 = 0.98) between the grafting degree (G) and conductance (G/wt% = (2.2 ± 0.1) 104c - (0.3 ± 0.4)) was determined in the range of 5 to 20% G, where a minimum stabilization time, such as 5 min, was required. Standard deviation of the G-value and the conductance decreased when a longer distance between the film and the lamp was used, leading to a more homogeneous surface modification. Therefore, we propose this system as a new method to monitor and predict the performance of UV-induced reactions.